HIV/AIDS in the Middle East and North Africa : The Costs of Inaction - Jenkins, Carol; Robalino, David A. (Washington, DC: World Bank, 2013)
This book reviews the human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) situation in the Middle East, North Africa, and Eastern Mediterranean (MENA/EM) region, and is intended to stimulate discussion and promote dialogue among the region's policy and decisionmakers. It seeks to provide a framework for multisectoral strategic action to reduce behaviors that risk spreading HIV, to care for and support those who become infected, and to diminish vulnerability among specific segments of society. Although most evidence suggests that overall HIV prevalence is low in the region, greater investments in improved surveillance, and care needed now-to maintain low prevalence levels and preserve the focus on national and regional development goals.